Ignorance as a productive response to epistemic perturbations. - Mays, Chris (Synthese, 2021)
This paper argues that ignorance, rather than being a result or representation of false beliefs or misinformation, is a compensatory epistemic adaptation of complex rhetoric systems. A rhetoric system is here defined as a set of interconnected rhetorical elements (beliefs, arguments, commonplaces [loci communes], meanings, and texts) that cohere into a self-organized system that is thoroughly "about" its contexts—meaning that its own boundaries and relations are both constrained and enabled by the contexts in which it exists. Ignorance, as described here, is epistemic management that preserves the boundaries and relations of a rhetoric system, and is a way of dealing with information that runs counter to one's beliefs. Ignorance is also productive, in that it produces new knowledge that works to make rhetoric systems more resistant to potential destabilization. To elaborate these points, the paper examines discourse about the phenomenon of global climate change, which illustrates how individuals productively counter information as a way of preserving beliefs. As the paper argues, ignorance is neither a cognitive nor epistemological failure, but rather is a result of the dynamic and continuous process of enforcing epistemic and rhetorical boundaries.